Therapeutic Approaches to Dysthymia (Global Journal of Medical Research, 2022)
Introduction: Dysthymia is a psychic disorder defined by chronic lowering of mood, with a minimum duration of two years, in which fluctuating moments of the emotional state occur. Unlike the clinical picture of "major depressions", dysthymia has milder manifestations, which occur in a non-episodic manner. Even with milder symptoms, dysthymia ends up having a significant impact on patients lives, since, in the vast majority of cases, the diagnosis is made too late. It is a disease that affects 3 to 6% of the world population, mainly individuals in early adulthood, being twice as common in women than in men. The prognosis of this psychic disorder is associated with the chronicity of the disease and the possible comorbidities resulting from the depressive condition.